PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN, KEBUDAYAAN, PEMUDA DAN OLAHRAGA KABUPATEN MAMUJU UTARA - Irwan, Andi (Katalogis, 2016)
This study aims to determine the effect of variable competencies (knowledge, skills, self-concept, personal characteristics and motives) on the performance of employees at the Department of Education, Culture, Youth and Sports Mamuju Utara and influence competency partially on employee performance: the effect of knowledge, skills, self-concept, personal characteristics and motives of the performance of employees at the Department of Education, Culture, Youth and Sports of North Mamuju regency. The population in this research that all employees are scattered on each unit of work / field / secretariat within the Department of Education, Culture, Youth and Sports of North Mamuju regency. The method used is a survey that is explonary causal relationship in the form of a survey which aims to find out the pattern of a causal relationship between the variables of competence with the performance by using multiple linear regression analysis. The results showed that the variables competencies (knowledge, skills, self-concept, personal characteristics and motives) simultaneously significant effect on employee performance. Partially, the variable most dominant influence of competence, namely the skills and self-concept is the smallest influence on the performance of employees at the Department of Education, Culture, Youth and Sports of North Mamuju regency.